Nanomaterials for environmental and energy applications prepared by solution combustion based-methodologies: Role of the fuel. (2017) - Deganello, Francesca
Abstract: Nanostructured materials are widely studied for environmental and energy-related applications. Solution combustion synthesis (SCS) is a very well-known methodology for the preparation of a large variety of inorganic nanomaterials. The fuel has a central role in the SCS, being able to influence several important properties of nanomaterials. In particular, optimization of the fuel type and amount allows tuning the textural, morphological and microstructural properties, but also the structural, electrical, redox, catalytic and surface ones. Moreover, the use of waste-derived fuels makes it an ecofriendly methodology and, at the same time, confers peculiar properties to the nanomaterial. Finally, the versatility of the solution combustion-based methodologies encourages finding advanced synthetic strategies for the production of tailored nanomaterials with novel multifunctional properties.